Dominant resistance against plant viruses - Dryas eDe Ronde; Patrick eButterbach; Richard eKormelink (Frontiers in Plant Science, 2014)
To establish a successful infection plant viruses have to overcome a defence system composed of several layers. This review will overview the various strategies plants employ to combat viral infections with main emphasis on the current status of single dominant resistance (R) genes identified against plant viruses and the corresponding avirulence (Avr) genes identified so far. The most common models to explain the mode of action of dominant R genes will be presented. Finally, in brief the hypersensitive response (HR) and extreme resistance (ER), and the functional and structural similarity of R-genes to sensors of innate immunity in mammalian cell systems will be described.